Addressing the social costs of international migration to Filipino families and children - Anonuevo, Augustus T. (2010)
International migration, albeit its benefits, has its social costs. With the feminization of international migration, it is expected that separation from migrant mothers would adversely affect a large number of families and children in the country. Empirical studies conducted on the social costs of migration in the country focused on the effects on children left behind by their migrant parents. These studies revealed some conflicting findings but were unanimous on the adverse effects of the physical abscence of migrant mothers on their children's emotional well-being, school performance and relationships with parents.

Programs and projects of the government, Catholic Church, and three NGOs that seek to address the social costs of international migration were assessed to be limited in scope and impact. There are, however, promising practices and initiatives by NGOs that need to be supported, replicated, and mainstreamed. This paper recommended that the Philippine government adopts the international migration and development and duality of international migration be integrated in the national and local development planning. National and local organizations were also proposed to be established to converge initiatives of government and civil society groups in addressing the social costs and in harnessing the development potential of international migrant of Filipinos.
Keywords: Migrations